2021
DOI: 10.3390/polym13040571
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Effects of Cellulose Nanocrystals and Sepiolite When Combined on Ionic Liquid Plasticised Chitosan Materials

Abstract: Cellulose nanocrystals (CNCs) and/or sepiolite (SPT) were thermomechanically mixed with un-plasticised chitosan and chitosan/carboxymethyl cellulose (CMC) blends plasticised with 1-ethyl-3-methylimidazolium acetate ([C2mim][OAc]). Examination of the morphology of these materials indicates that SPT aggregates were reduced when CNCs or [C2mim][OAc] were present. Inclusion of CNCs and/or SPT had a greater effect on material properties when the matrices were un-plasticised. Addition of SPT or CNCs altered the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Compared with isosorbide-plasticized films, glycerol-plasticized ones showed the absorption peak of -OH (at 1405 cm −1 ) appearing at a higher wavenumber position (blue shift), indicating there were stronger molecular interactions between glycerol and the biopolymers [19]. After the addition of GO, the two bands originally at 1544 cm −1 (N-H bending from amine and amide II) and 1068 cm −1 (asymmetric C-O-C stretching in the glycosidic linkage) were blue-shifted and there were two redshifts at 1025 cm −1 (C-O stretching) and 1634 cm −1 (amide I) [39,40]. For MMT-loaded biopolymers, two blue shifts (1068 cm −1 for C-O-C bonds and 1025 cm −1 for C-O bond) and one redshift (1634 cm −1 for amide I) were observed.…”
Section: Molecular Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with isosorbide-plasticized films, glycerol-plasticized ones showed the absorption peak of -OH (at 1405 cm −1 ) appearing at a higher wavenumber position (blue shift), indicating there were stronger molecular interactions between glycerol and the biopolymers [19]. After the addition of GO, the two bands originally at 1544 cm −1 (N-H bending from amine and amide II) and 1068 cm −1 (asymmetric C-O-C stretching in the glycosidic linkage) were blue-shifted and there were two redshifts at 1025 cm −1 (C-O stretching) and 1634 cm −1 (amide I) [39,40]. For MMT-loaded biopolymers, two blue shifts (1068 cm −1 for C-O-C bonds and 1025 cm −1 for C-O bond) and one redshift (1634 cm −1 for amide I) were observed.…”
Section: Molecular Interactionsmentioning
confidence: 99%
“…Table S1 shows the droplet images for the different samples at 0 s and 60 s. A lower WCA means higher surface hydrophilicity (higher surface free energy), which is primarily associated with the chemical groups exposed on the material surface [39]. All WCA values declined after a water drop was placed on the film surface for 60 s. Regarding the decreasing WCA with time, during wetting, water could disrupt biopolymer chain interactions on the material surface, leading to more free polar groups available to bind water [40]. In addition, the slight evaporation of water and the slow water uptake of the composite films (since both chitosan and gelatin are hydrophilic) may also lead to a slight decrease in WCA.…”
Section: Surface Hydrophilicitymentioning
confidence: 99%
“…Bendaoud et al have shown that [C 4 mim]Cl IL destroyed the biopolymeric crystal structure more efficiently when compared to diethylphthalate [73]. This same IL allows a faster de-structurization of the biopolymer during their processing, including starch, which reduces the energy required in this step and the formation of more homogeneous blends [70,71]. Similar results were observed when [Amim]Cl was used as a plasticizer for starch processing: lower glass transition temperatures (T g ) for processing the biopolymeric materials and the resulting materials presented lower water absorption [77,78].…”
Section: Ionic Liquids As Plasticizersmentioning
confidence: 99%
“…Since a water drop on the films greatly changed with time, WCA was measured at 0 s and 60 s. All the composite films displayed similar WCA values at 0 s (92-115°) and at 60 s (82-101°). Regarding the reduced WCA with time, during wetting, water could disrupt biopolymer chain interactions on the material surface, leading to more free polar groups available to bind water (Chen, Xie, Tang, & McNally, 2021a;Chen et al, 2021b). Among the biopolymer films, the 50CS group had the lowest WCA values, indicating higher surface hydrophilicity.…”
Section: Water Absorption and Surface Hydrophilicitymentioning
confidence: 99%